2021
DOI: 10.31234/osf.io/yuhaz
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A unified explanation of variability and bias in human probability judgments: How computational noise explains the mean-variance signature

Abstract: Human probability judgments are variable and subject to systematic biases. Sampling-based accounts of probability judgment have successfully explained such idiosyncrasies by assuming that people remember or simulate instances of events and base their judgments on sampled frequencies. Biases have been explained either by noise corrupting sample accumulation (the Probability Theory + Noise account), or as a Bayesian adjustment to the uncertainty implicit in small samples (the Bayesian sampler). While these two a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 27 publications
(54 reference statements)
1
15
0
Order By: Relevance
“…However, in a task in which participants were repeatedly asked to estimate the relative frequency of geometric objects on a screen, the variability of probability judgments peaked for probability estimates in the center of the range (i.e., close to 0.5), and was well described by a binomial distribution instead of a Gaussian distribution (Howe & Costello, 2020). While these results though were based on perceptual stimuli for which sensory noise could play a role, a later study found the same results when participants were estimating probabilities from memory, e.g., estimating the probability of rain on a random day in England, and also showed that additive Gaussian noise could not explain the inverted-u shape, even if responses were censored at the edges of the response range (see Figure 3A 1 and Figure 3A 2 ; Sundh et al, 2021).…”
Section: Non-gaussian Noisementioning
confidence: 77%
See 3 more Smart Citations
“…However, in a task in which participants were repeatedly asked to estimate the relative frequency of geometric objects on a screen, the variability of probability judgments peaked for probability estimates in the center of the range (i.e., close to 0.5), and was well described by a binomial distribution instead of a Gaussian distribution (Howe & Costello, 2020). While these results though were based on perceptual stimuli for which sensory noise could play a role, a later study found the same results when participants were estimating probabilities from memory, e.g., estimating the probability of rain on a random day in England, and also showed that additive Gaussian noise could not explain the inverted-u shape, even if responses were censored at the edges of the response range (see Figure 3A 1 and Figure 3A 2 ; Sundh et al, 2021).…”
Section: Non-gaussian Noisementioning
confidence: 77%
“…But substantial variability also occurs in tasks in which perceptual acuity is no barrier. For example, people's judgments of the probability of the same event vary from one occasion to another, even when no new information has been observed between judgments (Sundh et al, 2021). Even people's preferences between monetary gambles will show considerable variability over short periods of time (Loomes & Sugden, 1998;Mosteller & Nogee, 1951;.…”
Section: Noise In Cognition: Bug or Feature?mentioning
confidence: 99%
See 2 more Smart Citations
“…For small N, both models predict only a limited responses across trials on their mean response for each query type. Their findings suggest that earlier fits with Wasserstein distance may have produced biased results (Sundh et al, 2021). They reported evidence for the truncation of responses and a correlation between variance and shrinkage parameter estimates across participants.…”
Section: Prior Comparisons Of the Modelsmentioning
confidence: 92%